Awaiting MacArthur's return : World War II guerrilla resistance against the Japanese in the Philippines - Villanueva, James A. (James Alexander) (Modern war studies., 2022)
"Over the course of World War II, guerrillas from across the Philippines opposed Imperial Japan's occupation of the archipelago. Although the guerrillas never possessed the combat strength to overcome the Japanese occupation on their own, they disrupted operations, kept the spirit of resistance alive, provided important intelligence to the Allies, and assumed frontline duties fighting the Japanese. By examining the organization, motivations, capabilities, and operations of the guerrillas, James Villanueva argues that the guerrillas were effective because Japanese punitive measures, along with a strong sense of obligation and loyalty to the United States, pushed most of the population to support the guerrillas. Unlike their predecessors opposing the Americans in 1899, the guerrillas during World War II benefited from the leadership of American and Filipino military personnel and received significant aid and direction from General Douglas MacArthur's Southwest Pacific Area (SWPA) Headquarters, conducting one of the most effective and sophisticated resistance campaigns in World War II. Awaiting the Allies' Return is the first comprehensive examination of major World War II guerrilla groups across the Philippine Archipelago, providing a fuller picture of the nature of the war in the South and Southwest Pacific and revealing the extent to which the guerrilla movement affected operations throughout the area"--